2014
DOI: 10.1590/0103-6440201300049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Surfactant on the Antimicrobial Activity of Sodium Hypochlorite Solutions

Abstract: The objective of the present study was to evaluate the antimicrobial activity of sodium hypochlorite (NaOCl) associated with a surfactant. Seventy single-rooted extracted human teeth were inoculated with Enterococcus faecalis, and incubated for 21 days (37 °C). The groups were distributed according to the irrigation solution used during root canal preparation: 5%, 2.5% and 1% NaOCl; 5%, 2.5% and 1% Hypoclean®, a solution containing a surfactant (cetrimide) associated with NaOCl. Three microbiological samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…48,49 In studies reported by Bolfoni et al and Perez-Conesa, Mclandsborough and Weiss, the addition of surfactants, such as surfynol, centrimide and polypropylene glycol, showed greater antimicrobial activity of the antimicrobial agent. 50,51 Overall, our results reveal interesting antimicrobial activity for OPF against E. coli. Effectiveness towards this bacterial strain demonstrated the potential of black spruce extracts, since this gram-negative bacteria is generally more resistant to antimicrobial agents than gram-positive bacteria.…”
Section: Antimicrobial Activitymentioning
confidence: 64%
“…48,49 In studies reported by Bolfoni et al and Perez-Conesa, Mclandsborough and Weiss, the addition of surfactants, such as surfynol, centrimide and polypropylene glycol, showed greater antimicrobial activity of the antimicrobial agent. 50,51 Overall, our results reveal interesting antimicrobial activity for OPF against E. coli. Effectiveness towards this bacterial strain demonstrated the potential of black spruce extracts, since this gram-negative bacteria is generally more resistant to antimicrobial agents than gram-positive bacteria.…”
Section: Antimicrobial Activitymentioning
confidence: 64%
“…The authors tested different NaOCl solutions with and without cetrimide in the irrigation of 70 uniradicular human teeth contaminated by E. faecalis ; and observed that at the 7‐day period treatment, only the NaOCl associated with the surfactant‐treated specimens were bacterial contamination free. This result may be explained due to a possible residual effect of the surfactant molecule (Bolfoni et al, ). Cetrimide, a quaternary ammonium, has chemical activity similar to chlorhexidine, characterized by its substantivity (Bolfoni et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result may be explained due to a possible residual effect of the surfactant molecule (Bolfoni et al, ). Cetrimide, a quaternary ammonium, has chemical activity similar to chlorhexidine, characterized by its substantivity (Bolfoni et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies, using microbiological culture (Bolfoni et al . ), turbidity of culture medium measured by a UV spectrophotometer (Giardino et al . ), viability staining and confocal microscopy (Wang et al .…”
Section: Discussionmentioning
confidence: 99%